The Concept of Happiness in the Household: Al-Ghazali's Sufistic Perspective - Mubarok, M. Ali Mubarok; Desi, Desi Anggraeni; Nila, Nila Munana (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2025)
Problem statement: The concept of domestic happiness embodies the value of idealism. Idealism underscores the significance of the superiority of the mind, soul, or spirit over material possessions. Objective: This article aims to analyse the notion of happiness in Al-Ghazali's thought and the ways in which its implementation can foster harmony and well-being within domestic life. Methods: The methodology employed in this study is an analytical approach, utilising a literature review to examine Al-Ghazali's perspectives on happiness and the application of this concept in households, which is understood as the integration of Sufi values. Results: The findings indicate that, according to Al-Ghazali, happiness is achieved through self-awareness, followed by the knowledge of Allah SWT, attained through both knowledge and action, the cultivation of faith, the purification of the soul, and the perfection of one's spirit. Conclusion: The implementation of Sufistic materialism, as articulated by Al-Ghazali, posits that happiness within the household is realised when the home becomes a sanctuary for worship, facilitating closeness to Allah.